The Efficacy of Outsourced Employment Services for Adults Exiting Australian Prisons - Ollerton, Janice (International journal of offender therapy and comparative criminology, 2024)
Crime rates in Australia have declined or been steady over the past decade yet prison populations are at all-time highs. Similarly, unemployment rates have been low but unemployment for those ex-prisoners seeking work is very high. In this paper, we draw on the findings of an Australia-wide survey of government-funded employment service providers who support working-aged Australians including ex-prisoners in their search for work. We find that the heterogeneity of the needs of ex-prisoners coupled with the frugality and inflexibility of government policies and practices frustrates the abilities of these agencies to provide services to this target group.